Proverbs and preaching Sermons in Pre-Islamic Poetry and their indications Peacefulness - أ.م.د.علاء جاسم جابر (College of Education for Women, 2019)
Proverbs and preaching Sermons in Pre-Islamic Poetry and their indications Peacefulness